2023
DOI: 10.1097/dss.0000000000003750
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Efficacy of a Dual CO2 and 1570-nm Hybrid Laser for Periorbital Rejuvenation

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…While there is currently no accepted gold standard, fractional ablative and non‐ablative lasers are among the most popular options 1,9 . The combination of both techniques in one system offers the superior efficacy of ablative treatment, along with the faster healing time and minimal discomfort associated with non‐ablative methods, and has proven beneficial for a variety of skin conditions 7,8,10,11 . In conclusion, findings from this study demonstrate the potential of the hybrid fractional laser system as a safe and effective method to achieve satisfactory aesthetic results with minimal downtime, making it a promising treatment approach for SD.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…While there is currently no accepted gold standard, fractional ablative and non‐ablative lasers are among the most popular options 1,9 . The combination of both techniques in one system offers the superior efficacy of ablative treatment, along with the faster healing time and minimal discomfort associated with non‐ablative methods, and has proven beneficial for a variety of skin conditions 7,8,10,11 . In conclusion, findings from this study demonstrate the potential of the hybrid fractional laser system as a safe and effective method to achieve satisfactory aesthetic results with minimal downtime, making it a promising treatment approach for SD.…”
Section: Discussionmentioning
confidence: 70%
“…The development of hybrid fractional laser devices allows clinicians to effectively treat a wide range of indications, taking advantage of the benefits of both ablative and non‐ablative lasers 7 . More recently, Tsur‐Shenhav et al 8 . have demonstrated that a single‐pass treatment with a dual CO 2 and 1,570 nm hybrid fractional laser yielded impressive clinical outcomes in periorbital rejuvenation in 24 patients, with a strong safety profile and a relatively simple recovery.…”
Section: Introductionmentioning
confidence: 99%
“…However, a relatively long recovery (5.9 ± 1.7 days) was described. 17 In the search for a more balanced procedure, this study used the same side-by-side lasing mode, to compare the safety and efficacy of a single high-setting treatment versus 2-3 low-moderate-setting treatments for facial rejuvenation. In most parameters, a superiority was found to the latter.…”
Section: Discussionmentioning
confidence: 99%
“…The side‐by‐side (AFL & NAFL in different pixels) mode was evaluated in a recent publication that reported a 26%–50% improvement in the periorbital area after a single pass treatment. However, a relatively long recovery (5.9 ± 1.7 days) was described 17 …”
Section: Discussionmentioning
confidence: 99%
“…Combinations of thulium 1940 nm and diode 1550 nm (Candela® Nordlys Frax Pro), CO 2 and 1570 nm (Alma Hybrid™), or erbium and 1470 nm (Sciton HALO™) have shown good efficacy in skin rejuvenation. [24][25][26] Laser resurfacing is also increasingly being used to help improve the absorption and efficacy of transepidermal drug delivery of more hydrophilic actives by breaching the lipophilic stratum corneum. 28 However, this treatment concept is limited by molecular size, lipid solubility and the formulation of the drug.…”
Section: Epidermal Resurfacing and Skin Tighteningmentioning
confidence: 99%